Trajectory-Based Safety Analysis of Electric Battery Taxis - Yan Zhuang; Ning Li; Chunjiao Dong; Penghui Li; Bo Xu; Miaoyan Yang (Journal of Advanced Transportation)
This paper utilizes trajectory data of electric taxis in Shenzhen to first study the driving characteristics of electric taxis from different indicators such as travel/driving speed, overspeed ratio, and overspeed amplitude. A combination weighting VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) evaluation method based on Nash equilibrium is constructed to comprehensively assess the operation safety of electric taxis in various spatiotemporal scenarios. The results show that the average driving speed and overspeed amplitude of battery electric taxis is 39.14 km/h and 22.78%, which is 1.27 and 1.72 times that of fuel taxis. The average overspeed ratio, average acceleration and deceleration and total acceleration and deceleration frequency are all more than twice those of fuel taxis. The average acceleration, deceleration, and idle time ratios of battery electric taxis are 0.27, 0.24 and 0.43, respectively, with a constant speed time ratio of only 0.06. The proposed combination weighting VIKOR evaluation method outperforms other evaluation methods in comprehensively considering data discreteness and correlation. Electric taxis have the highest operational safety on arterial roads, while the safety on minor arterial roads and local roads is relatively poor, especially on weekends. In all spatiotemporal scenarios, the overall operation safety of electric taxis is lower than that of fuel taxis. The research results can provide theoretical support for the formulation of effective measures and policies to reduce dangerous driving behavior of electric taxis.